About elementary particles - V. Yu. Stetsenko (Литьë и металлургия, 2023)
It is shown that only stable particles can be elementary particles. The fundamental elementary particles are positive, negative and neutral particles of space. Photons and neutrinos are formed from them, which are elementary particles of electrons, positrons and protons. A neutral photon consists of a positive elementary particle of space, around which a negative elementary particle of space rotates. A neutrino consists of a negative elementary particle of space, around which a positive elementary particle of space rotates. An electron has a structure consisting of negative and neutral photons connected by negative elementary particles of space. The positron has a structure consisting of positive and neutral photons connected by negative elementary particles of space. A proton consists of a positively charged nucleus around which electrons rotate. The proton nucleus consists of positrons bound by neutrino particles. Atomic nuclei consist of positive and neutral protons connected by the exchange of electrons and neutrino particles. The carriers of electromagnetic interaction are positive and negative elementary particles of space. The carriers of the gravitational interaction are neutral elementary particles of space. Electromagnetic, gravitational and inertial forces are the forces of space. Space is an equilibrium system, just like the whole universe.